Abdominal Pregnancy in the Small Intestine Presenting as Acute Massive Lower Gastrointestinal Hemorrhage - Apiradee Pichaichanlert; Vor Luvira; Nakhon Tipsunthonsak (Case Reports in Surgery)
An abdominal pregnancy is an ectopic pregnancy in which the implantation site occurs in the abdominal cavity outside the female reproductive organs. There have been four reported cases that ruptured into the gastrointestinal tract and into the large intestine. We present the first case of an abdominal pregnancy rupturing into the small intestine with a good outcome.